The Influence of Work Engagement on Employee Performance at PT. Telkom Indonesia Tbk., Witel Malang Through Organizational Citizenship Behavior as a Mediation Variable - Lintang Kamulyanisa Hadi; Rifki Hanif (International Journal of Science, Technology & Management, 2022)
Companies engaged in the service sector are strongly influenced by employee performance. The company will always try to develop employee performance so that company goals can be achieved. Getting employees who have high performance for the company is not an easy thing because it takes several factors that need to be contributed by employees to the company, including work engagement and organizational citizenship behavior. This study uses a quantitative research approach with analysis. The type of research used is explanatory research with survey methods. Data obtained through participant observation, interviews, and filling out questionnaires to a sample of 40 employees of PT. Telkom Indonesia Tbk., Witel Malang using a saturated sample from the customer care department. The instrument which consists of 18 statement items uses a Likert scale and five alternative answers. With the results of data analysis, it can be seen that work engagement affects employee performance through organizational citizenship behavior. While the work engagement variable does not directly affect employee performance